Global Regolith Thermophysical Properties of the Moon From the Diviner Lunar Radiometer Experiment. Issue 12 (4th December 2017) - Hayne, Paul O.; Bandfield, Joshua L.; Siegler, Matthew A.; Vasavada, Ashwin R.; Ghent, Rebecca R.; Williams, Jean‐Pierre; Greenhagen, Benjamin T.; Aharonson, Oded; Elder, Catherine M.; Lucey, Paul G.; Paige, David A.
Abstract: We used infrared data from the Lunar Reconnaissance Orbiter (LRO) Diviner Lunar Radiometer Experiment to globally map thermophysical properties of the Moon's regolith fines layer. Thermal conductivity varies from 7.4 × 10 −4  W m −1  K −1 at the surface to 3.4 × 10 −3  W m −1  K −1 at depths of ~1 m, given density values of 1, 100 kg m −3 at the surface to 1, 800 kg m −3 at 1 m depth. On average, the scale height of these profiles is ~7 cm, corresponding to a thermal inertia of 55 ± 2 J m −2  K −1  s −1/2 at 273 K, relevant to the diurnally active near‐surface layer, ~4–7 cm. The temperature dependence of thermal conductivity and heat capacity leads to an ~2 times diurnal variation in thermal inertia at the equator. On global scales, the regolith fines are remarkably uniform, implying rapid homogenization by impact gardening of this layer on timescales <1 Gyr. Regional‐ and local‐scale variations show prominent impact features <1 Gyr old, including higher thermal inertia (> 100 J m −2  K −1  s −1/2 ) in the interiors and ejecta of Copernican‐aged impact craters and lower thermal inertia (< 50 J m −2  K −1  s −1/2 ) within the lunar cold spots identified by Bandfield et al. (2014). Observed trends in ejecta thermal inertia provide a potential tool for age dating craters of previously unknown age, complementary to the approach suggested by Ghent et al. (2014). Several anomalous regions are identified in the global 128 pixels per degree maps presented here, including a high‐thermal inertia deposit near the antipode of Tycho crater. Plain Language Summary: We measured the Moon's temperature cycles with the Lunar Reconnaissance Orbiter's Diviner instrument to make the first global maps of important physical properties of the dusty surface layer. These maps reveal a rich new view of the last billion years of impact processes and volcanism on the Moon. Impacts by meteorites cause the breakdown of rocks and accumulation of regolith—the granular surface materials. Our results show that regolith formation is a rapid process, which homogenizes and redistributes fine particles over large distances. These new observations provide a wealth of data for future study and also suggest a new technique for determining the ages of craters on the Moon and other planetary surfaces, using temperatures to infer the depth of accumulated regolith. Key Points: We present global maps of regolith thermophysical properties The Moon's upper ~4–7 cm of regolith has a globally averaged thermal inertia of ~55 J m −2  K −1  s −1/2 at a reference temperature of 273 K The upper lunar regolith is remarkably uniform, with the upper ~10 cm homogenized on >1 Gyr timescales